2019
DOI: 10.1002/eco.2182
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of habitat hydraulic model outputs to DTM and computational mesh resolution

Abstract: In this study, a state‐of‐the‐art approach in modelling fish habitats, using high‐resolution topographical data, obtained from unmanned aerial vehicle, was applied. Habitat Suitability Indices are used to predict how changes in discharge affect instream fish habitats. Habitat Suitability Indices regarding depth and velocity for two size classes (small sized fish 5–15 cm total length and large sized >15 cm total length) of Salmo pelagonicus and Barbus balcanicus were used, in combination with a two‐dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…The assessment of hydropeaking alterations via ERHPs or habitat modelling is sensitive to the accuracy in the simulated flow variables. Model performance in turn may be affected by model dimensionality (e.g., Brown & Pasternack, 2009), resolution of the domain discretization (e.g., Papaioannou et al, 2020), but also by river morphological complexity or discharge conditions (e.g., Hauer et al, 2013; Legleiter, Kyriakidis, McDonald, & Nelson, 2011). We found that for a given morphology and flow condition, the mean absolute errors (MAE) of flow velocities simulated with the 1D models are larger than those simulated with any of the considered 2D models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of hydropeaking alterations via ERHPs or habitat modelling is sensitive to the accuracy in the simulated flow variables. Model performance in turn may be affected by model dimensionality (e.g., Brown & Pasternack, 2009), resolution of the domain discretization (e.g., Papaioannou et al, 2020), but also by river morphological complexity or discharge conditions (e.g., Hauer et al, 2013; Legleiter, Kyriakidis, McDonald, & Nelson, 2011). We found that for a given morphology and flow condition, the mean absolute errors (MAE) of flow velocities simulated with the 1D models are larger than those simulated with any of the considered 2D models.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations regarding the required model dimensionality and spatial resolutions are established for different ERHPs and with respect to the morphological complexity of the river reach under consideration. When comparing 1D and 2D hydrodynamic models as input for a hydropeaking impact analysis we hypothesize that the hydrodynamic modelling results (flow velocities and flow depths) exhibit increasing accuracy by increasing the (a) model dimensionality (1D/2D); (Pasternack et al, 2006) and (b) spatial resolution of the computational domain (Ghamry & Katopodis, 2017; Horritt, Bates, & Mattinson, 2006; Papaioannou, Papadaki, & Dimitriou, 2020). Therefore, we assume that the finest resolved 2D model provides the most accurate solution and use this as the reference scenario (benchmark).…”
Section: Introductionmentioning
confidence: 99%
“…This model has been successfully utilised to simulate hydraulic habitats, which demonstrated its efficiency for simulating physical habitats. More details on using HEC-RAS 2D to simulate habitat hydraulic addresses have been in the literature (Papaioannou et al, 2020). However, Figure 3 shows the workflow of HEC-RAS 2D for simulating depth and velocity distribution in this study.…”
Section: Physical Habitat Modelmentioning
confidence: 99%
“…Another useful and applicable index to measure system performance was mean absolute error (MAE) which is displayed in Eq. (4) [32] Moreover, we used NSE that is initially used to assess the predictive power of hydrological models [33]. Equation (5) displays definition of NSE in the present study.…”
Section: Testing Processmentioning
confidence: 99%